2019
DOI: 10.29252/beat-070209
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Transforaminal Epidural Steroid Injection in Patients with Lumbar Radicular Pain; Outcome Results of 2-Year Follow-Up

Abstract: Objective: To evaluate the effectiveness of transforaminal lumbar epidural steroid injections (TFESI) in patients with unilateral radiculopathy due to lumbar intervertebral disc protrusion regarding pain intensity, functional disability, current opioid intake and patients’ satisfaction. Methods: The study is conducted in a pain management center (Tehran, Iran), during 2018. Inclusion criteria were age ≥18 years, radiculopathy for more than 6 months due to imagine-proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Although mixed, some studies suggest that ESI may reduce opioid use in the short term. 79 , 80 Although no corticosteroids have received FDA approval for epidural injection, numerous studies over the past 50 years have demonstrated efficacy and safety leading to high utilization in treating lumbosacral radiculopathy. Overall, complication rates are low, with vasovagal reactions, increased radicular pain, and pain at the injection site being the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mixed, some studies suggest that ESI may reduce opioid use in the short term. 79 , 80 Although no corticosteroids have received FDA approval for epidural injection, numerous studies over the past 50 years have demonstrated efficacy and safety leading to high utilization in treating lumbosacral radiculopathy. Overall, complication rates are low, with vasovagal reactions, increased radicular pain, and pain at the injection site being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…ESIs play an integral role as part of a multimodal treatment strategy to treat lumbar and cervical radicular pain and theoretically present fewer risks than surgical interventions. Although mixed, some studies suggest that ESI may reduce opioid use in the short term 79,80. Although no corticosteroids have received FDA approval for epidural injection, numerous studies over the past 50 years have demonstrated efficacy and safety leading to high utilization in treating lumbosacral radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[330][331][332] Epidural steroids are effective in reducing pain severity, decreasing opioid use, improving function, avoiding the need for surgery, and even treating pain in patients who have not responded to surgical intervention. 329,[333][334][335][336][337] Steroids may exert anti-inflammatory effects on the neuroimmune interface. Consistently with preclinical models, steroid administration (local, intrathecal, or systemic administration) before or at the time of injury reduces proinflammatory cytokines, neuronal firing rates, glial cell activation in the spinal cord, and correlates with a reduction in pain behavior after nerve injury.…”
Section: Steroids and Neuro-immune Interfacementioning
confidence: 99%
“…It is associated with the significant disability. [3][4] It was observed in literature that transforaminal route of epidural injection for management of pain of lumbar region can be more helpful in resolution of pain. But not much work was done in this regard and conservative management was still in practice.…”
Section: Introductionmentioning
confidence: 99%